2018
DOI: 10.1021/acs.organomet.8b00568
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline Earth Metal Compounds of Methylpyridinato β-Diketiminate Ligands and Their Catalytic Application in Hydroboration of Aldehydes and Ketones

Abstract: Ever increasing demand for green and sustainable chemical processes has set up a drive to replace transition metals with earth-abundant, nontoxic, and environmentally benign alternatives. In this regard, the alkaline earth metal complexes have attracted significant attention. Herein, we have used a β-diketiminato ligand with methyl-pyridine side arm to synthesize magnesium (1) and calcium (2) compounds. The constitutions of 1 and 2 have been confirmed by single crystal X-ray studies, which show that the magnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 59 publications
1
34
0
Order By: Relevance
“…Such catalytic efficiency of 1 – 3 and fast conversion of the substrates may be related to their coordinatively unsaturated nature. Perhaps due to this unsaturation in coordination sites the conversion requires less time in comparison to previously reported homoleptic alkaline earth metal catalysts [12d] . Since the catalysts 1 – 3 are enantiopure, one might expect enantiomeric excess in the product.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Such catalytic efficiency of 1 – 3 and fast conversion of the substrates may be related to their coordinatively unsaturated nature. Perhaps due to this unsaturation in coordination sites the conversion requires less time in comparison to previously reported homoleptic alkaline earth metal catalysts [12d] . Since the catalysts 1 – 3 are enantiopure, one might expect enantiomeric excess in the product.…”
Section: Resultsmentioning
confidence: 86%
“…The hydroboration catalysts based on alkaline earth metals reported so far are mostly heteroleptic in nature [12b,e,f, 17] . The homoleptic catalysts for this chemical transformation are extremely rare possibly due to saturation in coordination sites [12d] . With this background, one of the goals of our study was to probe a performance of tetra coordinated complexes 1 – 3 as catalysts for hydroboration of ketones.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the traditional mechanism where the metal hydride acts as an active catalyst, very recently, various research groups have reported the use of a Lewis acid‐based mechanism for the hydroboration of carbonyl compounds ,. [18c], …”
Section: Resultsmentioning
confidence: 99%
“…There are reports that a limited catalyst was used for the chemoselective reduction of aldehydes over other active functional groups such as ‐NH 2 , ‐OH, esters, amides, and nitriles , ,. [33a], …”
Section: Introductionmentioning
confidence: 99%